Extinção da punibilidade nos crimes de sonegação fiscal sob a égide da lei nº. 8.137/90: uma proteção deficiente da ordem tributária - Dantas, Francisca Matias Ferreira (2012)
The current study has two goals. The first one analyses the juridical treatment against the Tax Order according to the Brazilian legislation , mainly the Law number 8.137/1990, in which the corpus of analyses , of the types of tributary crime it is , specifically tax evasion written on the 1º and 2º of the Law number 8.137/1990 , studying the beginning and the development of the tax offence and its ontological aspects , due to penal punishment , the significance principle act and its extinctive cause of punishment , focusing on the penalty under legal prevision of the article 34 of the Law 9.249/1995 , that revaluated referred form , before repealed from the texts of the Law which issued the matter. The second goal aims to study the divergence on the moment the payment should be done under doctrinaire view, Judicature and the position of the Federal Supreme Court, the Justice and their divergent points. To make this research, an evaluation of the efficacy of the Civil Law was made, its influence to work on the tributary obligation public safe reimbursement and taxpayer owed after dilation. As a result, it was considered the existence of a weak punitive system in relation to the crimes mentioned , thus it goes against the constitutional scope; the reform requirement that allows real implementation of the Democratic Law State and thus prevent tax evasion growth in the country